Meningkatkan Kecerdasan Keuangan Anak TK Muslimat : Sosialisasi Celengan Target Dengan Metode SISCA - Rahmawati, Diah; Zahidah, Saifty Rahma; Agustina, Prafasta Vika; Adinugraha, Hendri Hermawan; Stiawan, Drajat (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this service activity is to provide training and educate students about the benefits and importance of saving. This service activity uses the socialization method. The majority of children in the Muslimat Salafiyah NU Purwosari Kindergarten are not familiar with the culture of saving. Whereas saving literacy and education is very important for early childhood. Therefore, socialization of financial management for children needs to be done to minimize consumptive behavior as well as efforts to educate children to manage their funds effectively. It can be concluded that the children of Muslimat Salafiyah NU Purwosari Kindergarten do not have the habit of saving. With the socialization of the Target Piggy Bank through the SISCA method, it is hoped that it can increase knowledge and saving habits in children.